REPO SISI MAJELIS PERMUSYAWARATAN RAKYAT DALAM PERUBAHAI\ UUD T945 - A. Rosyid Al Atok (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2010)
Abstract: this paper aims to describe the repositioning of the people's consultative assembly (mpr) after the 1945 changes. There are at least four experienced reposition the country's institutions. Mpr is no longer the incamation of all the people. Mpr limited authority. The presence of mpr loss provisions and konsepsualnya juridical basis. And the assembly is no longer the parliament.